王鳳儀倫理療病闡析——儒家生命倫理之活例: On Fengyi Wang’s Ethical Cure - A Living Example of Confucian Life Ethics - ZHANG, Xianglong (International Journal of Chinese & Comparative Philosophy of Medicine, 2014)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 本文首先介紹王鳳儀的人生，說明其開悟體驗如何塑成他的倫理療病術，並闡釋這種不尋常醫術的特點、哲理基礎、具體方法和一些案例，繼而分析倫理療病的作用機制和條件、它與中醫和西醫的相通與不同處，以及它的適用範圍。另外，本文還集中介紹王鳳儀的追隨者――劉有生對此術的繼承和發展。最後，文章總述這種倫理療病術的儒家性，表明倫理療病可以直接作用於人的生命倫理學。 First, this paper presents the life of Feng-yi Wang (1864-1937), a peasant thinker who lived in northeastern China and shows how Wang’s experiences of enlightenment enabled him to invent an ethical cure. A serious disease with which Wang had been afflicted for more than 10 years was healed overnight by his sudden recognition that the origin of his illness was not the immorality of his brothers but his own hatred for them and by his profound repentance for this mistake. As a result of this experience, he realized that no universal principles exist for family relationships. Wang underwent two more experiences of enlightenment: the first during a desperate attempt to save a moral friend, and the second during three years spent besides his father’s tomb as an expression of filial love. Second, the characteristics, philosophical foundations and concrete applications of this unusual therapy are explained and some examples are provided. Wang identified the causes of illnesses in disorders of family and other ethical relations, and treated these illnesses by correcting the corresponding ethical disorders. Wang proposed that every human life has three dimensions, heavenly, psychological and desirous. Disease occurs when an individual’s heavenly disposition is obscured or damaged by passionate emotions arising from psychological states and/or desire. It has been argued that Wang regarded the heavenly dimension of human nature as embodied in family bonds, exemplified by the parent-child relationship. Wang’s method of treatment had three steps. First, the patient was encouraged to recognize the potentially fatal nature of her/his situation, and thus to speak with complete sincerity and commitment to finding a cure. Second, the patient’s way of life, especially her/his familial and other ethical relationships, were examined to determine the cause of her/his illness. Third, the patient was told why his/her behavior toward others was immoral and urged to repent thoroughly in front of the offended party, whether a living family member or an ancestor’s memorial tablet. Physical reactions to the treatment such as vomiting and weeping were taken as signs that the method had worked and the illness had been alleviated or cured. The third aim of this paper is to identify the mechanisms of Wang’s ethical treatment, the conditions for its success and the scope of its application. According to the Doctrine of the Mean, complete sincerity is the necessary condition for Wang’s treatment to succeed. A timely and skillful diagnosis arouses a patient’s conscience and encourages her/him to speak sincerely. Therefore, adequate communication is necessary between the diagnostician and the patient. Although Wang’s ethical treatment may seem better suited to psychic than physical ailments, Wang’s followers argue that it can be used to cure physical injuries. In the third section of the paper, Wang’s ethical approach is briefly compared with traditional Chinese medicine and modern Western medicine. Fourth, attention is paid to one of Wang’s followers, You-sheng Liu. In the fifth and final section of the paper, the Confucian properties of Wang’s ethical treatment are described and his approach to medicine is shown to directly affect the ethics of human life. DOWNLOAD HISTORY | This article has been downloaded 468 times in Digital Commons before migrating into this platform.